Propuesta de mejora con fines de reducción de desperdicios en las secciones de perecederos en un almacén de grandes superficies en Bogotá D.C. (2021)
In Colombia, approximately 34% of the total available food is lost and wasted in the different stages of the food chain. In the distribution link, large-scale stores lose around 2 million tons; There are internal and external regulations for these warehouses, however the percentage of waste continues to increase. The objective of this study is to make a proposal for improvement through the use of quality tools and techniques in order to reduce food waste in the perishable sections of a large-scale warehouse in the city of Bogotá. Initially, a diagnosis is made and the root causes that originate the problem are analyzed. Subsequently, the improvement plan is presented. The results show that the main causes of the problem are associated with labor, machinery and methods, being the 5S, SMED, TPM and Kaizen tools of Lean Manufacturing the most appropriate to eliminate the potential causes identified.